Experimental Investigation of the Effect of Two-Stage Peltier Application on the Temperature of a Microprocessor - Fatih Uysal; Sinan Çobaner (Sakarya University Journal of Computer and Information Sciences)
Increasing the number of transistors to enhance the performance of processors leads to overheating, creating a need for cooling. Traditional cooling methods with copper pipes are becoming outdated and insufficient, prompting the development of alternative cooling methods. In this study, a two stage Peltier module cooler was designed using Peltier modules, and its performance in cooling the processor was evaluated. The two stage Peltier module was created by thermally connecting two Peltier modules in series and tested under different experimental conditions. In the first experiment, the manufactured two-stage Peltier module was placed in the experimental setup with its surfaces exposed to air. Both the cold and hot surfaces were in contact with air, allowing heat transfer through natural convection. Afterward, power was supplied, and the surface temperatures were observed, and with the application of power, it was observed that the temperature of the hot surface increased from 34.8°C to 110.2°C, while the temperature of the cold surface rise from 24.2°C to 67.1°C. In the second experiment, a heat sink and a fan were mounted on the hot surface of the two stage Peltier module to evaluate cooling performance. As a result of these experiments, it was observed that with the application of the cooler, the minimum cold surface temperature dropped to -2.3°C, while the maximum hot surface temperature reached 26°C. In the third experiment, the Peltier modules cooling performance was tested on a micro heater instead of air. In these experiments, four different powers were applied to the micro-heater, and at the maximum power of 9.9 W, the lowest cold surface temperature observed was 126.4 °C. Finally, the two stage Peltier module system was directly applied to a computer processor to observe its cooling performance under real-use conditions. The experiments showed that the two stage Peltier module cooler reduced the processor temperature. In addition, under the same ambient conditions, it was observed that computer cooler reduced the microprocessor temperature to 62°C, while the cooler using the two-stage Peltier module reduced the microprocessor temperature to 43°C at the same microprocessor clock speed.It was determined that as power was supplied to the Peltier module, the temperature difference between the two surfaces increased, but there was no significant change in the temperature of the hot surface. Additionally, it was observed that the performance of the Peltier module varied with different power values. The article demonstrates that the two stage Peltier module can be used as an effective solution for processor cooling applications.